Reading Wars: An Overview of the U.S. Educational Policy - Budiraharjo, Markus (LLT Journal: A Journal on Language and Language Teaching, 2012)
Educational scholars generally agree that educational policies are inevitably regarded as one of the most contested areas in education. On the one hand, democracy requires more involvement on the part of the citizens. At the most ideal level, democratic mechanisms have been developed to allow more people to more fruitfully participate in decision making. It follows that the political mechanisms would entail better policies, which represent the voices of any people. On the other hand, politics seems to run against this ideal. Policy making is highly convoluted with economy and political trade-offs. Drawing on debates over the phonic vs. whole-language policies in the U.S. in the past four or five decades, this paper sets to discuss the complexity of politics and language policy. A growing awareness of the complexity of politics and policy making is certainly a pressing need for those working in the area of English Education.